Plasma membrane and brain dysfunction of the old: Do we age from our membranes? - Martín, Mauricio G.; Dotti, Carlos G. (Frontiers in Cell and Developmental Biology, 2022)
One of the characteristics of aging is a gradual hypo-responsiveness of cells to extrinsic stimuli, mainly evident in the pathways that are under hormone control, both in the brain and in peripheral tissues. Age-related resistance, i.e. reduced response of receptors to their ligands, has been shown to Insulin and also to leptin, thyroid hormones and glucocorticoids. In addition, lower activity has been reported in aging for ß-adrenergic receptors, adenosine A2B receptor, and several other G-protein-coupled receptors. One of the mechanisms proposed to explain the loss of sensitivity to hormones and neurotransmitters with age is the loss of receptors, which has been observed in several tissues. Another mechanism that is finding more and more experimental support is related to the changes that occur with age in the lipid composition of the neuronal plasma membrane, which are responsible for changes in the receptors’ coupling efficiency to ligands, signal attenuation and pathway desensitization. In fact, recent works have shown that altered membrane composition - as occurs during neuronal aging - underlies reduced response to glutamate, to the neurotrophin BDNF, and to insulin, all these leading to cognition decay and epigenetic alterations in the old. In this review we present evidence that altered functions of membrane receptors due to altered plasma membrane properties may be a triggering factor in physiological decline, decreased brain function, and increased vulnerability to neuropathology in aging.